EFFECT OF INJECTED DIFFERENT CONCENTRATIONS OF ALCOHOLIC EXTRACT OF Moringa oleifera LEAVES POWDER IN HATCHING EGGS OF ADVANCED AGE OF BROILER BREEDERS ON PRODUCTIVE PERFORMANCE AND CARCASSES OF BROILER CHICKENS: EFFECT OF INJECTED DIFFERENT CONCENTRATIONS OF ALCOHOLIC EXTRACT OF Moringa oleifera LEAVES POWDER IN HATCHING EGGS OF ADVANCED AGE OF BROILER BREEDERS ON PRODUCTIVE PERFORMANCE AND CARCASSES OF BROILER CHICKENS (Iraqi Journal of Market Research and Consumer Protection, 2022)
This experiment was conducted to study the effect of injecting hatching eggs into a flock of broiler aged mothers with different concentrations of the alcoholic extract of Moringa oleifera powder on productive performance of broilers during the period of rearing of 35 days. The study included two experiments for a period at 2/10/2021 to 28/11/2021, where eggs were injected into the Mustafa Poultry Hatchery/ Wasit Governorate- Aziziyah District. A 400 hatching eggs of 308 Ross  mothers of modern broilers used at age  of 48  week, eggs of average weight  66 ± 1 g/egg were collected in same day then stored for two days. A quarter of treatments were randomly distributed with 100 eggs for each treatment. The first treatment T1 without injection as control treatment, and T4, T3, and T2 (while injected into the space air) on day 12 of, in an amount of 0.2 mL for each egg, with concentration of 450, 300, 150 µg/mL, respectively. The hatched chicks were bred in the same fields, where 180 chicks of the chicks were distributed into four treatments, 45 chicks for each treated and three replicates (15 chicks) for each T1, T2, T3 and T4  were placed in a cage for 35 days. The results Showed A significant  (p